A semi-aromatic polyester and its preparation method and application

By controlling the hydroxyl content in the semi-aromatic polyester, the problems of difficulty in degradation of existing aromatic polyesters and poor compatibility with PBAT and polylactic acid are solved, and the preparation of high-strength and tear-resistant film materials are achieved.

CN116023636BActive Publication Date: 2025-03-25JIANGSU KINGFA SCI & TECH ADVANCED MATERIALS CO LTD +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202111249166.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-10-26
Publication Date
2025-03-25
Estimated Expiration
2041-10-26

AI Technical Summary

Technical Problem

The existing aromatic polyesters are difficult to degrade after use, and the compatibility between PBAT and polylactic acid is poor, resulting in limited toughening modification effect.

Method used

By controlling the hydroxyl content in the semi-aromatic polyester, especially the hydroxyl content connected to the aliphatic dicarboxylic acid and the aromatic dicarboxylic acid is controlled at 17-40 mmol/kg, and the total hydroxyl content is controlled at 35-80 mmol/kg, to improve its compatibility with materials such as polylactic acid.

Benefits of technology

The compatibility of semi-aromatic polyester and polylactic acid and other materials is significantly improved, and a high-strength, tear-resistant film material is obtained.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116023636B_ABST
    Figure CN116023636B_ABST
Patent Text Reader

Abstract

The invention discloses a semi-aromatic polyester and a preparation method and application thereof. By controlling the hydroxyl content in the semi-aromatic polyester, in particular controlling the content of hydroxyl groups connected to aliphatic dicarboxylic acids in the semi-aromatic polyester to 17-40 mmol / kg, the content of hydroxyl groups connected to aromatic dicarboxylic acids in the semi-aromatic polyester to 17-40 mmol / kg, and controlling the total hydroxyl content to 35-80 mmol / kg, the compatibility of the semi-aromatic polyester with materials such as polylactic acid can be significantly improved, thereby obtaining a high-strength, tear-resistant film material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of biodegradable polyesters, and in particular to a semi-aromatic polyester with a specific hydroxyl content and a preparation method and application thereof. Background Art

[0002] Thermoplastic aromatic polyesters widely used in industry and daily life have excellent thermal stability and mechanical properties, are easy to process and are inexpensive. For example, polyethylene terephthalate (PET) and polybutylene terephthalate (PBT) have been widely used in the manufacture of fibers, films and containers. However, these aromatic polyesters are difficult to degrade after use and disposal, and no obvious direct degradation of aromatic polyesters such as PET and PBT by microorganisms has been observed so far. In order to combine the excellent properties of aromatic polyesters, since the 1980s, those skilled in the art have been committed to the research of synthesizing aliphatic-aromatic copolyesters, that is, introducing aromatic segments into aliphatic polyesters.

[0003] The representative of aromatic polyester is PBAT, but its tensile strength is low and its modulus is low. The disadvantages in mechanical strength limit the application of PBAT and require modification.

[0004] Polylactic acid (PLA) is an aliphatic polyester obtained from bio-based raw materials such as potatoes, cassava, and corn starch through biological fermentation and chemical synthesis. It has good biocompatibility and biodegradability, excellent mechanical strength, transparency and processability, and is therefore widely used in the fields of medicine, packaging films, and disposable daily necessities. However, polylactic acid is brittle and has poor toughness, making it difficult to promote and apply in many fields.

[0005] PBAT and PLA exhibit completely different mechanical properties, so the two are often used as complementary materials for blending and modification, that is, PLA is used as the matrix and PBAT is used to toughen and modify polylactic acid, or PBAT is used as the matrix and PLA is used to strengthen and modify PBAT. The final modification effect depends on the compatibility of the two. However, due to the poor compatibility between PBAT and polylactic acid, these toughening modifiers can only slightly improve the impact strength of PLA, and it is often difficult to improve the ductility of PLA at the same time. Summary of the invention

[0006] To solve the above problems, the purpose of the present invention is to provide a semi-aromatic polyester, which has a specific hydroxyl content and can significantly improve the compatibility of the semi-aromatic polyester with materials such as polylactic acid, thereby obtaining a high-strength, tear-resistant film material.

[0007] Another object of the present invention is to provide a method for preparing the semi-aromatic polyester.

[0008] The above-mentioned purpose of the present invention is achieved through the following technical solutions:

[0009] A semi-aromatic polyester derived from repeating units consisting of:

[0010] The first component A, based on the total molar amount of the first component A, comprises:

[0011] a1) 40-60 mol % of at least one aliphatic dicarboxylic acid or a derivative thereof;

[0012] a2) 40-60 mol % of at least one aromatic dicarboxylic acid or a derivative thereof;

[0013] Second component B: 1,4-butanediol;

[0014] The content of hydroxyl groups connected to aliphatic dicarboxylic acid in the semi-aromatic polyester is 17-40 mmol / kg; the content of hydroxyl groups connected to aromatic dicarboxylic acid in the semi-aromatic polyester is 17-40 mmol / kg; and the total content of hydroxyl groups is 35-80 mmol / kg.

[0015] In the polyester synthesis process, due to the influence of many factors such as the different raw material monomer structures or proportions, the different types of catalysts, branching agents and chain extenders, the preparation process, the reaction time, the polymerization temperature, etc., the molecular structure of the polyester finally prepared is quite different. The present invention has found through research that the hydroxyl content in the semi-aromatic polyester can affect the compatibility of the semi-aromatic polyester with materials such as polylactic acid. If the hydroxyl content is too high or too low, the compatibility of the semi-aromatic polyester with materials such as polylactic acid is poor.

[0016] The present invention unexpectedly discovered through research that by controlling the hydroxyl content in the semi-aromatic polyester, especially controlling the content of hydroxyl groups connected to aliphatic dicarboxylic acids in the semi-aromatic polyester to 17-40 mmol / kg, controlling the content of hydroxyl groups connected to aromatic dicarboxylic acids in the semi-aromatic polyester to 17-40 mmol / kg, and controlling the total hydroxyl content to 35-80 mmol / kg, the compatibility of the semi-aromatic polyester with materials such as polylactic acid can be significantly improved, thereby obtaining a high-strength, tear-resistant film material.

[0017] In the present invention, the component a1) aliphatic dicarboxylic acid or its derivative is selected from one or a mixture of oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, 1,11-undecanedicarboxylic acid, 1,10-decanedicarboxylic acid, undecanedicarboxylic acid, 1,12-dodecanedicarboxylic acid, hexadecanedicarboxylic acid, eicosanedicarboxylic acid or tetracosanedicarboxylic acid or their ester derivatives or their anhydride derivatives.

[0018] As a specific example, the component a1) is selected from oxalic acid, dimethyl oxalate, malonic acid, dimethyl malonate, succinic acid, dimethyl succinate, methylsuccinic acid, glutaric acid, dimethyl glutarate, bis(2-hydroxyethyl) glutarate, bis(3-hydroxypropyl) glutarate, bis(4-hydroxybutyl) glutarate, 2-methylglutaric acid, 3-methylglutaric acid, adipic acid, dimethyl adipate, bis(2-hydroxyethyl) adipate, bis(3-hydroxypropyl) adipate, bis(4-hydroxybutyl) adipate, 3-methyladipic acid, 2,2,5,5-tetramethyladipic acid, pimelic acid, suberic acid, azelaic acid, dimethyl azelate, sebacic acid, 1,11-undecanedicarboxylic acid, 1,10-decanedicarboxylic acid, undecanedicarboxylic acid, One or more of 1,12-dodecanedicarboxylic acid, hexadecanedioic acid, eicosanedicarboxylic acid, tetracosanedicarboxylic acid, dimer acid and ester derivatives thereof or anhydride derivatives thereof, preferably one or more of succinic acid, adipic acid, sebacic acid, 1,12-dodecanedicarboxylic acid and ester derivatives thereof or anhydride derivatives thereof, more preferably one or two of adipic acid, sebacic acid or ester derivatives thereof or anhydride derivatives thereof, most preferably adipic acid or ester derivatives thereof or anhydride derivatives thereof.

[0019] In the present invention, the component a2) aromatic dicarboxylic acid or its derivative is selected from terephthalic acid, isophthalic acid, naphthalene dicarboxylic acid or its ester derivatives or its anhydride derivatives or a mixture of several thereof, preferably terephthalic acid or its ester derivatives or its anhydride derivatives.

[0020] As a specific example, the component a2) is selected from terephthalic acid, dimethyl terephthalate, bis(2-hydroxyethyl) terephthalate, bis(3-hydroxypropyl) terephthalate, bis(4-hydroxybutyl) terephthalate, isophthalic acid, dimethyl isophthalate, bis(2-hydroxyethyl) isophthalate, bis(3-hydroxypropyl) isophthalate, bis(4-hydroxybutyl) isophthalate, 2,6-naphthalene dicarboxylic acid, dimethyl 2,6-phthalate, 2,7-naphthalene dicarboxylic acid, dimethyl 2,7-phthalate, 3,4′- Diphenyl oxide dicarboxylic acid, 3,4′ diphenyl oxide dicarboxylic acid dimethyl ester, 4,4′-diphenyl oxide dicarboxylic acid, 4,4′-diphenyl oxide dicarboxylic acid dimethyl ester, 3,4′-phenylene sulfide dicarboxylic acid, 3,4′-phenylene sulfide dicarboxylic acid dimethyl ester, 4,4′-diphenyl sulfide dicarboxylic acid, 4,4′-phenylene sulfide dicarboxylic acid dimethyl ester, 3,4′-diphenyl sulfone dicarboxylic acid, 3,4′-diphenyl sulfone dicarboxylic acid dimethyl ester, 4,4′-diphenyl sulfone dicarboxylic acid, 4,4′-diphenyl sulfone dicarboxylic acid dimethyl ester, 3,4′-benzophenone dicarboxylic acid, 3,4′-benzophenone dicarboxylic acid dimethyl ester, 4,4′-benzophenone dicarboxylic acid, 4,4′- One or more of dimethyl benzophenone dicarboxylate, 1,4-naphthalene dicarboxylic acid, dimethyl 1,4-naphthalene dicarboxylate, 4,4′-methylene bis(benzoic acid), 4,4′-methylene bis(dimethyl benzoate) or their ester derivatives or their anhydrides, preferably terephthalic acid or its ester derivatives or their anhydride derivatives.

[0021] In the present invention, if necessary, the semi-aromatic polyester further contains a third component C, wherein the third component C is preferably a compound containing at least three functional groups, preferably a compound containing three to six functional groups, preferably selected from: one or more of tartaric acid, citric acid, malic acid, trimethylolpropane, trimethylolethane, pentaerythritol, polyether triol, glycerol, 1,3,5-trimethylol acid, 1,2,4-trimethylol acid, 1,2,4-trimethylol anhydride, 1,2,4,5-pyromellitic acid and pyromellitic dianhydride, more preferably trimethylolpropane, pentaerythritol or glycerol.

[0022] Based on the total molar amount of the first component A, the content of the third component C is 0.01-5.0 mol%, preferably 0.02-2.0 mol%.

[0023] The semi-aromatic polyester may further include a fourth component D, wherein the fourth component D is a chain extender.

[0024] The chain extender is one or a mixture of isocyanate, isocyanurate, peroxide, epoxide, oxazoline, oxazine, lactam, carbodiimide or polycarbodiimide containing two or more functional groups.

[0025] The isocyanate containing two or more functional groups may be an aromatic isocyanate or an aliphatic isocyanate, preferably an aromatic diisocyanate or an aliphatic diisocyanate. Preferably, the aromatic diisocyanate is toluene 2,4-diisocyanate, toluene 2,6-diisocyanate, diphenylmethane 2,2'-diisocyanate, diphenylmethane 2,4'-diisocyanate, diphenylmethane 4,4'-diisocyanate, naphthalene 1,5-diisocyanate or xylene diisocyanate.

[0026] More preferably, the aromatic diisocyanate is diphenylmethane 2,2'-diisocyanate, diphenylmethane 2,4'-diisocyanate or diphenylmethane 4,4'-diisocyanate.

[0027] The isocyanate containing two or more functional groups may also be tris(4-isocyanato-phenyl)methane having three rings.

[0028] Preferably, the aliphatic diisocyanate is any linear or branched alkylene diisocyanate or cycloalkylene diisocyanate containing 2 to 20 carbon atoms, more preferably containing 3 to 12 carbon atoms. The aliphatic diisocyanate can be hexamethylene 1,6-diisocyanate, isophorone diisocyanate or methylene di(4-isocyanatocyclohexane), most preferably hexamethylene 1,6-diisocyanate or isophorone diisocyanate.

[0029] Preferably, the isocyanurate containing 2 or more functional groups is an aliphatic isocyanurate, which is derived from an alkylene diisocyanate or cycloalkylene diisocyanate having 2 to 20 carbon atoms, preferably 3 to 12 carbon atoms, such as isophorone diisocyanate or methylene di(4-isocyanatocyclohexane). The alkylene diisocyanate may be a linear or branched compound. Particularly preferred are isocyanurates based on cyclic trimers, pentamers or higher oligomers of n-hexamethylene diisocyanate, such as hexamethylene 1,6-diisocyanate.

[0030] Preferably, the peroxide containing two or more functional groups is preferably benzoyl peroxide, 1,1-di(tert-butylperoxy)-3,3,5-trimethylcyclohexane, 1,1-di(tert-butylperoxy)methylcyclododecane, 4,4-di(butylperoxy)butyl valerate, dicumyl peroxide, tert-butyl peroxybenzoate, dibutyl peroxide, α,α-di(tert-butylperoxy)diisopropylbenzene, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, 2,5-dimethyl-2,5-di(tert-butylperoxy)hex-3-yne or tert-butyl peroxide cumene.

[0031] Preferably, the epoxide containing two or more functional groups is preferably hydroquinone, diglycidyl ether, resorcinol diglycidyl ether, 1,6-hexanediol diglycidyl ether, hydrogenated bisphenol A diglycidyl ether, terephthalic acid diglycidyl ester, tetrahydrophthalic acid diglycidyl ester, hexahydrophthalic acid diglycidyl ester, phthalic acid dimethyl diglycidyl ester, phenylene diglycidyl ether, ethylene diglycidyl ether, trimethylene diglycidyl ether, tetramethylene diglycidyl ether, hexamethylene diglycidyl ether. diglycidyl ether, sorbitol diglycidyl ether, polyglycerol polyglycidyl ether, pentaerythritol polyglycidyl ether, diglycerol polyglycidyl ether, glycerol polyglycidyl ether, trimethylolpropane polyglycidyl ether, resorcinol diglycidyl ether, neopentyl glycol diglycidyl ether, ethylene glycol diglycidyl ether, diethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, dipropylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether or poly-1,4-butylene glycol diglycidyl ether.

[0032] The epoxide containing 2 or more functional groups is also preferably a copolymer based on styrene, acrylate and / or methacrylate and containing epoxy groups, and the epoxy groups are preferably glycidyl methacrylate. Advantageous compounds have been shown to be copolymers in which the proportion of glycidyl methacrylate in the copolymer is higher than 20% by weight, more preferably higher than 30% by weight, more preferably higher than 50% by weight. The epoxy equivalent weight in these copolymers is preferably 150 to 3000 g / equivalent, more preferably 200 to 500 g / equivalent. The weight average molecular weight Mw of the copolymer is preferably 2000 to 25000, more preferably 3000 to 8000. The number average molecular weight Mn of the copolymer is preferably 400 to 6000, more preferably 1000 to 4000. The polydispersity index (Q=Mw / Mn) is preferably 1.5 to 5.

[0033] The oxazoline or oxazine containing two or more functional groups is preferably dioxazoline or dioxazine, and the bridging part thereof is a single bond, (CH2)z-alkylene, wherein z=2, 3 or 4, such as methylene, 1,2-diyl, 1,3-diyl or 1,2-diyl, or phenylene. Specifically, the dioxazoline is 2,2'-di(2-oxazoline), di(2-oxazoline)methane, 1,2-di(2-oxazoline)ethane, 1,3-di(2-oxazoline)propane or 1,4-di(2-oxazoline)butane, 2,2'-di(2-oxazoline), 2,2'-di(4-methyl-2-oxazoline), 2,2'-di(4,4'-dimethyl-2-oxazoline), 2,2'-bis(4-ethyl-2-oxazoline), 2,2'-bis(4,4'-diethyl-2-oxazoline), 2,2'-bis(4-propyl-2-oxazoline), 2,2'-bis(4-butyl-2-oxazoline), 2,2'-bis(4-hexyl-2-oxazoline), 2,2'-bis(4-phenyl-2-oxazoline), 2,2'-bis(4-cyclohexyl-2-oxazoline), 2,2' -bis(4-benzyl-2-oxazoline), 2,2'-p-phenylenebis(4-methyl-2-oxazoline), 2,2'-p-phenylenebis(4,4'-dimethyl-2-oxazoline), 2,2'-m-phenylenebis(4-methyl-2-oxazoline), 2,2'-m-phenylenebis(4,4'-dimethyl-2-oxazoline), 2,2'-hexamethylenebis(2-oxazoline), 2,2 '-octamethylenebis(2-oxazoline), 2,2'-decamethylenebis(2-oxazoline), 2,2'-ethylenebis(4-methyl-2-oxazoline), 2,2'-tetramethylenebis(4,4'-dimethyl-2-oxazoline), 2,2'-9,9'-diphenoxyethanebis(2-oxazoline), 2,2'-cyclohexylenebis(2-oxazoline) or 2,2'-diphenylene(2-oxazoline).

[0034] More preferred is 1,4-di(2-oxazolinyl)benzene, 1,2-di(2-oxazolinyl)benzene or 1,3-di(2-oxazolinyl)benzene.

[0035] Specifically, the dioxazine is 2,2′-di(2-dioxazine), di(2-dioxazinyl)methane, 1,2-di(2-dioxazinyl)ethane, 1,3-di(2-dioxazinyl)propane, 1,4-di(2-dioxazinyl)butane, 1,4-di(2-dioxazinyl)benzene, 1,2-di(2-dioxazinyl)benzene or 1,3-di(2-dioxazinyl)benzene.

[0036] The carbodiimide or polycarbodiimide containing two or more functional groups is preferably N,N′-di-2,6-diisopropylphenylcarbodiimide, N,N′-di-o-tolylcarbodiimide, N,N′-diphenylcarbodiimide, N,N′-dioctyldecylcarbodiimide, N,N′-di-2,6-dimethylphenylcarbodiimide, N-tolyl-N′-cyclohexylcarbodiimide, N,N′-di-2,6-di-tert-butylphenylcarbodiimide, N-tolyl-N′-phenylcarbodiimide, N,N′-di-p-nitrophenylcarbodiimide, N,N'-di-p-aminophenylcarbodiimide, N,N'-di-p-hydroxyphenylcarbodiimide, N,N'-dicyclohexylcarbodiimide, N,N'-di-p-tolylcarbodiimide, p-phenylenebis-o-tolylcarbodiimide, p-phenylenebis-dicyclohexylcarbodiimide, hexamethylenebis-dicyclohexylcarbodiimide, 4,4'-dicyclohexylmethanecarbodiimide, ethylenebis-diphenylcarbodiimide, N,N'-benzyl-carbodiimide, N-octadecyl-N'-phenylcarbodiimide, N-benzyl-N'-phenylcarbodiimide, N-octadecyl N-phenyl-N'-tolylcarbodiimide, N-cyclohexyl-N'-tolylcarbodiimide, N-phenyl-N'-tolylcarbodiimide, N-benzyl-N'-tolylcarbodiimide, N,N'-di-o-ethylphenylcarbodiimide, N,N'-di-p-ethylphenylcarbodiimide, N,N'-di-o-isopropylphenylcarbodiimide, N,N'-di-p-isopropylphenylcarbodiimide, N,N'-di-o-isobutylphenylcarbodiimide, N,N'-di-p-isobutylphenylcarbodiimide, N,N'-di-2,6-diethylphenylcarbodiimide , N,N′-di-2-ethyl-6-isopropylphenylcarbodiimide, N,N′-di-2-isobutyl-6-isopropylphenylcarbodiimide, N,N′-di-2,4,6-trimethylphenylcarbodiimide, N,N′-di-2,4,6-triisopropylphenylcarbodiimide, N,N′-di-2,4,6-triisopropylphenylcarbodiimide, N,N′-di-2,4,6-triisobutylphenylcarbodiimide, diisopropylcarbodiimide, dimethylcarbodiimide, diisobutylcarbodiimide, dioctylcarbodiimide, tert-butylisopropylcarbodiimide, di-β-naphthylcarbodiimide or di-tert-butylcarbodiimide.

[0037] Preferably, the content of the fourth component D is 0.01-5 mol % based on the total molar amount of the first component A.

[0038] Preferably, the semi-aromatic polyester has a viscosity of 150-350 ml / g as measured in a phenol / o-dichlorobenzene solution with a weight ratio of 1:1 in a constant temperature water bath at 25±0.05° C. according to GB / T 17931-1999.

[0039] Preferably, the semi-aromatic polyester has a carboxyl content of 5-50 mmol / kg, preferably 10-30 mmol / kg.

[0040] The present invention also provides a method for preparing the semi-aromatic polyester, comprising the following steps:

[0041] S1. a1 in the first component A and the second component B are added to the slurry preparation kettle according to a proportion, and the prepared slurry is transported to the first esterification reactor, and the refluxed second component B and the catalyst are added to the first esterification reactor from another route, and the esterification reaction is carried out at 150-200°C and 30-110kPa for 2-4h to obtain the esterification product Ba1; a2 in the first component A and the second component B are added to the slurry preparation kettle according to a proportion, and the prepared slurry is transported to the second esterification reactor, and the refluxed second component B and the catalyst are added to the second esterification reactor from another route, and the esterification reaction is carried out at 200-250°C and 30-110kPa for 2-4h to obtain the esterification product Ba2;

[0042] S2. The esterification product Ba1 in step S1 is subjected to a primary polycondensation reaction at a reaction temperature of 170-220°C and a pressure of 1-10 kPa; the esterification product Ba2 in step S1 is subjected to a primary polycondensation reaction at a reaction temperature of 230-270°C and a pressure of 1-10 kPa; the two are subjected to a primary polycondensation reaction independently until the viscosity of each reaction product reaches 15-60 ml / g as specified in GB / T 17931-1999 in a phenol / o-dichlorobenzene solution with a weight ratio of 1:1 and measured in a constant temperature water bath at 25±0.05°C, to obtain primary polycondensation reaction products Pre-Ba1 and Pre-Ba2, respectively;

[0043] S3. The product Pre-Ba1 of the primary polycondensation reaction obtained in step S2 is transferred to the first final polymerization kettle, the reaction temperature is 180-230°C, and the pressure is 10-500Pa; the product Pre-Ba2 of the primary polycondensation reaction obtained in step S2 is transferred to the second final polymerization kettle, the reaction temperature is 220-270°C, and the pressure is 10-500Pa; the two are independently subjected to polycondensation reaction until the reaction product reaches the viscosity of 50-180 ml / g measured in a phenol / o-dichlorobenzene solution with a weight ratio of 1:1 and a constant temperature water bath at 25±0.05°C as specified in GB / T17931-1999, to obtain final polymerization products Poly-Ba1 and Poly-Ba2 respectively;

[0044] S4. The final polymerization products Poly-Ba1 and Poly-Ba2 obtained in step S3 are mixed and reacted in a mixer to obtain a semi-aromatic polyester having a viscosity of 150-300 ml / g as specified in GB / T 17931-1999 measured in a phenol / o-dichlorobenzene solution with a weight ratio of 1:1 in a constant temperature water bath at 25±0.05°C.

[0045] The pressures described in the process of the present invention are all absolute pressures (absolute pressures).

[0046] Preferably, in S1, when preparing the Ba2 esterification product, 0.001-1% of a catalyst based on the weight of the final semi-aromatic polyester is added. Preferably, the amount of the catalyst added is 0.02-0.2% of the weight of the final semi-aromatic polyester. Controlling the amount of catalyst added can make the subsequent processing more stable. Further, the catalyst can be a tin compound, an antimony compound, a cobalt compound, a lead compound, a zinc compound, an aluminum compound or a titanium compound, more preferably a zinc compound, an aluminum compound or a titanium compound, and most preferably a titanium compound. Titanium compounds such as tetrabutyl orthotitanate or tetraisopropyl orthotitanate have an advantage over other compounds in that the residual amount remaining in the product or downstream product is less toxic. This property is particularly important in biodegradable polyesters because they enter the environment directly in the form of compost bags or mulch films.

[0047] In S1, the total molar amount of the second component B is usually 1.1-3.0 times that of the first component A. The excess second component B is recovered through a purification device (usually a distillation tower) connected to the esterification reactor and then enters the esterification reactor. The amount of the recovered second component B is usually 20-50wt% of the amount of the fresh second component B.

[0048] In S2, when preparing the Pre-Ba1 prepolymer, the reaction temperature is more preferably 180-200°C, and the reaction pressure is more preferably 2-5 kPa.

[0049] In step S2, when preparing the Pre-Ba2 prepolymer, if necessary, the remaining amount of catalyst in step S1 can be added in step S2. The reaction temperature is more preferably 240-260°C, and the reaction pressure is more preferably 2-5 kPa.

[0050] In S2, when Pre-Ba1 and Pre-Ba2 are prepared respectively, the general reaction time is 2-5h. Under normal circumstances, after this reaction time, the primary polycondensation reaction products Pre-Ba1 and Pre-Ba2 with a viscosity of 15-60 ml / g measured in a phenol / o-dichlorobenzene solution with a weight ratio of 1:1 and a constant temperature water bath at 25±0.05℃ as specified in GB / T 17931-1999 can be produced. The carboxyl content of the primary polycondensation reaction products Pre-Ba1 and Pre-Ba2 after the S2 reaction is generally 10-60mmol / kg.

[0051] In the polycondensation reaction step of S3, if necessary, a passivating agent can be mixed with the pre-polyester. Available passivating agents are generally phosphorus compounds, including phosphoric acid, phosphorous acid and esters thereof. Based on the weight of the final polyester, the amount of the passivating agent is generally 0.001-0.1wt%, preferably 0.01-0.05wt%.

[0052] In S3, when preparing Poly-Ba1 polyester, the reaction temperature is more preferably 190-220° C., and the reaction pressure is more preferably 50-200 Pa.

[0053] In S3, when preparing Poly-Ba2 polyester, the reaction temperature is more preferably 240-260°C, and the reaction pressure is more preferably 20-100Pa.

[0054] In S3, the polycondensation reaction time is preferably 1-5h, more preferably 2-4h. The viscosity of the produced Poly-Ba1 and Poly-Ba1 polyesters measured in a phenol / o-dichlorobenzene solution with a weight ratio of 1:1 in a constant temperature water bath at 25±0.05°C according to GB / T 17931-1999 is 50-180ml / g. In addition, the carboxyl content of the Poly-Ba1 and Poly-Ba1 polyesters after the S3 reaction is generally 5-60 mmol / kg, and more preferably 10-30mmol / kg.

[0055] In S4, the mixing of Poly-Ba1 and Poly-Ba2 is carried out in a mixer, the mixer includes a raw material injection system, a temperature adjustment system, a high shear homogenization pump and a homogenizer; the temperature range of the mixer is 200°C-280°C, preferably 240°C-260°C; the residence time of Poly-Ba1 and Poly-Ba2 in the mixer is 1-4h, preferably 1.5-2h. After passing through the mixer, the reaction product reaches the viscosity of 150-300ml / g measured in a phenol / o-dichlorobenzene solution with a weight ratio of 1:1 in a constant temperature water bath at 25±0.05°C as specified in GB / T 17931-1999.

[0056] Preferably, if necessary, the method further comprises S5. adding the semi-aromatic polyester obtained in step S4 to the fourth component D to carry out a chain growth reaction at a reaction temperature of 200 to 270° C., with a reaction residence time of 0.5 to 15 minutes, preferably 2 to 5 minutes, until the reaction product reaches a viscosity of 150 to 350 ml / g as specified in GB / T 17931-1999 in a phenol / o-dichlorobenzene solution with a weight ratio of 1:1 and measured in a constant temperature water bath at 25±0.05° C., to obtain the product.

[0057] The present invention also provides the use of the semi-aromatic polyester in preparing a compostable product, wherein the compostable product may be a fiber, a film or a container.

[0058] The present invention also provides a semi-aromatic polyester molding composition, which comprises the following components by weight ratio:

[0059] 5-95wt% of the above-mentioned semi-aromatic polyester;

[0060] 5-95wt% additives and / or other polymers;

[0061] 0-70wt% reinforcement materials and / or fillers.

[0062] As a specific option, the additive and / or other polymer may be at least one or more components selected from aliphatic polyester, polycaprolactone, starch, cellulose, polyhydroxyalkanoate and polylactic acid.

[0063] Compared with the prior art, the present invention has the following beneficial effects:

[0064] The invention provides a semi-aromatic polyester. By controlling the hydroxyl content in the semi-aromatic polyester, in particular controlling the content of hydroxyl groups connected to aliphatic dicarboxylic acids in the semi-aromatic polyester to 17-40 mmol / kg, the content of hydroxyl groups connected to aromatic dicarboxylic acids in the semi-aromatic polyester to 17-40 mmol / kg, and controlling the total hydroxyl content to 35-80 mmol / kg, the compatibility of the semi-aromatic polyester with materials such as polylactic acid can be significantly improved, thereby obtaining a high-strength, tear-resistant film material. BRIEF DESCRIPTION OF THE DRAWINGS

[0065] Figure 1 1H NMR of PBAT obtained by the reaction of terephthalic acid, adipic acid and 1,4-butanediol measured by Bruker AV 500 nuclear magnetic resonance spectrometer;

[0066] Figure 2 It is the peak corresponding to the CH2 in the hydroxyl group connected to adipic acid and the hydroxyl group connected to terephthalic acid in PBAT. DETAILED DESCRIPTION

[0067] Unless otherwise specified, raw materials, reagents and solvents used in the present invention are all purchased commercially without any treatment. Below in conjunction with embodiment, the present invention is described in further detail, but embodiments of the present invention are not limited by following examples, and any other changes, modifications, substitutions, combinations, simplifications made without departing from the spirit and principle of the present invention should all be equivalent replacement modes, and are all included in protection scope of the present invention. In addition, about "part", "%" in this specification, unless otherwise specified, represent "mass parts", "mass %" respectively.

[0068] Performance testing method:

[0069] Test of hydroxyl content in semi-aromatic polyester (taking polybutylene adipate / terephthalate (PBAT) obtained in Example 1 as an example):

[0070] 20 mg of the semi-aromatic polyester sample was dissolved in 0.6 ml of deuterated chloroform, and then 1H NMR was measured at room temperature using a Bruker AV 500 nuclear magnetic resonance spectrometer, with the chloroform solvent peak calibrated at 7.26 ppm.

[0071] References: Chen, X.; Chen, W.; Zhu, G.; Huang, F.; Zhang, J., Synthesis, 1H-NMR characterization, and biodegradation behavior of aliphatic– aromatic random copolyester. J. Appl. Polym. Sci. 2007,104(4): 2643-2649. ) It can be seen that the four hydrogen atoms of the benzene ring in the terephthalic acid repeating unit appear at around 8.10 ppm; the four hydrogen atoms of the two CH2 units adjacent to the carbonyl group in the adipic acid repeating unit appear at around 2.33 ppm. Figure 1 Thus, the molar content of the diacid component can be expressed by the integrated areas (IT and IA) of the two peaks at 8.10 ppm and 2.33 ppm:

[0072] Terephthalic acid molar content in PBAT = IT / (IT+IA)×100%

[0073] Adipic acid molar content in PBAT = IA / (IT+IA)×100%

[0074] References: (Herrera, R.; Franco, L.; Rodríguez-Galán, A.; Puiggalí, J., Characterization and degradation behavior of poly(butylene adipate-co-terephthalate)s. J. Polym. Sci., Part A: Polym. Chem. 2002, 40(23): 4141-4157), the CH2 adjacent to the hydroxyl group connected to adipic acid appears at around 3.68 ppm, and the CH2 adjacent to the hydroxyl group connected to terephthalic acid appears at 3.74 ppm.

[0075] Depend on Figure 2 Computable,

[0076] The content XA (in mmol / kg) of hydroxyl groups connected to aliphatic dicarboxylic acid (adipic acid) in semi-aromatic polyester PBAT is:

[0077] (1)

[0078] The content XT (in mmol / kg) of the hydroxyl groups connected to the aromatic dicarboxylic acid (terephthalic acid) in the semi-aromatic polyester PBAT is:

[0079] (1)

[0080] The total hydroxyl content X is:

[0081] X=XA+XT

[0082] in,

[0083] I1 is the integrated area of ​​the two hydrogen atom peaks on the CH2 adjacent to the hydroxyl group connected to terephthalic acid;

[0084] I2 is the integrated area of ​​the two hydrogen atom peaks on the CH2 adjacent to the hydroxyl group connected to adipic acid;

[0085] IT is the integrated area of ​​the four hydrogen atoms on the benzene ring of the repeating unit of terephthalic acid;

[0086] IA is the integrated area of ​​the four hydrogen atoms on the two -CH2- groups connected to the carbonyl group of the adipic acid repeating unit;

[0087] M is the average molecular weight of the repeating unit of the semi-aromatic polyester PBAT. The molar ratio of terephthalic acid to adipic acid in Example 1 is 0.468:0.532, and the average molecular weight M of the repeating unit is: M=0.468*MPBT+0.532*MPBA. Among them, MPBT is the molecular weight of the PBT repeating unit of 220 g / mol; MPBA is the molecular weight of the PBA repeating unit of 200 g / mol; then the average molecular weight of the repeating unit of the semi-aromatic polyester PBAT in Example 1 is M=209 g / mol.

[0088] Viscosity number of semi-aromatic polyester:

[0089] According to GB / T 17931-1999, the sample concentration is 5 mg / ml in a phenol / o-dichlorobenzene solution with a weight ratio of 1:1 in a constant temperature water bath at 25±0.05℃.

[0090] Carboxyl content:

[0091] First, the acid value AN (mg KOH / g) is determined according to DIN EN 12634 of October 1998, and then the carboxyl content (mmol / kg) = (AN / 56) × 103. The solvent mixture used includes 1 volume part of DMSO, 8 volume parts of isopropanol, and 7 volume parts of toluene, and the solvent volume is 100 ml. Take 3-6 g of semi-aromatic polyester and heat it to 70℃ to dissolve all polymers into a clear solution. During the titration, the solution temperature is kept at 60-70℃ to avoid polymer precipitation. Tetrabutylammonium hydroxide is used as the titrant, and the highly toxic tetramethylammonium hydroxide is avoided. At the same time, in order to prevent the mixed solvent from absorbing CO2 in the air and thus affecting the volume of the blank solvent consumed titrant, when testing the volume of the blank solvent consumed titrant, the blank solvent should be heated to 70℃ and kept at a constant temperature for 0.5 h, and then the blank solvent should be titrated immediately with alkaline solution to prevent the blank solvent from further absorbing CO2 in the air after heating.

[0092] Tear Strength:

[0093] The obtained polyester composition was blown into a film on a double air ring film blowing machine with a film thickness of 20 μm. The air volumes of the inner air ring and the outer air ring were controlled between 1:1 and 1:3, and the blowing ratio was 2.5 to 4.0.

[0094] According to GB / T 1040.3-2006 Determination of tensile properties of plastics Part 3: Test conditions for films and sheets, the transverse tensile strength and longitudinal tensile strength are measured respectively.

[0095] According to GB / T 16578.2-2009 Determination of tear resistance of plastic film and sheeting Part 2: Elmendorf method, the longitudinal and transverse tear strength and longitudinal tear strength are measured respectively.

[0096] Embodiment 1:

[0097] S1. 355 kg / h of adipic acid and 328 kg / h of 1,4-butanediol are continuously added to the slurry preparation kettle, and the prepared slurry is continuously fed into the first esterification reactor. The flow rate of 1,4-butanediol from the bottom of the process tower is 109 kg / h. At the same time, 0.49 kg / h of glycerol and 0.179 kg / h of n-butyl titanate are added. The pressure of the reactor is controlled to be 40 kPa (absolute pressure), the temperature is 190° C., the residence time is 2-4 h, and the water, tetrahydrofuran and butanediol generated by the reaction are removed to obtain an ester Ba1;

[0098] 355 kg / h of terephthalic acid and 289 kg / h of 1,4-butanediol were continuously added to the slurry preparation kettle, and the prepared slurry was continuously fed into the second esterification reactor. The flow rate of 1,4-butanediol from the bottom of the process tower was 96 kg / h. At the same time, 0.43 kg / h of glycerol and 0.331 kg / h of n-butyl titanate were added. The pressure of the reactor was controlled to be 40 kPa (absolute pressure), the temperature was 240°C, the residence time was 2-4 hours, and the water, tetrahydrofuran and butanediol generated by the reaction were removed to obtain the ester Ba2;

[0099] S2. The esterified product Ba1 is transferred into the first pre-polycondensation reactor, and 0.077 kg / h of n-butyl titanate and 0.198 kg / h of triphenyl phosphate are added at the same time. The temperature is 200°C, the pressure of the reactor is 4 kPa, the residence time is 2-3 hours, and the excess butanediol is extracted. At this time, the reaction product Pre-Ba1 reaches the viscosity number of 45 ml / g measured in a phenol / o-dichlorobenzene solution with a weight ratio of 1:1 in a constant temperature water bath at 25±0.05°C as specified in GB / T 17931-1999;

[0100] The esterified product Ba2 was transferred into the second pre-polycondensation reactor, and 0.142 kg / h of n-butyl titanate and 0.356 kg / h of triphenyl phosphate were added at the same time. The temperature was 250°C, the pressure of the reactor was 2 kPa, the residence time was 2-3 hours, and the excess butanediol was extracted. At this time, the reaction product Pre-Ba2 reached the viscosity of 35 ml / g measured in a phenol / o-dichlorobenzene solution with a weight ratio of 1:1 in a constant temperature water bath at 25±0.05°C as specified in GB / T 17931-1999;

[0101] S3. The prepolymer Pre-Ba1 is fed into the first final polymerization kettle through a melt pump. The temperature of the first final polymerization kettle is 220°C, the pressure is 120Pa, and the reaction time is 3-4 hours. At this time, the reaction product Poly-Ba1 reaches the viscosity of 146 ml / g measured in a phenol / o-dichlorobenzene solution with a weight ratio of 1:1 in a constant temperature water bath at 25±0.05°C as specified in GB / T 17931-1999;

[0102] The prepolymer Pre-Ba2 is fed into the second final polymerization kettle through a melt pump. The temperature of the second final polymerization kettle is 250°C, the pressure is 20Pa, and the reaction time is 3-4 hours. At this time, the reaction product Poly-Ba2 reaches the viscosity of 135 ml / g measured in a phenol / o-dichlorobenzene solution with a weight ratio of 1:1 in a constant temperature water bath at 25±0.05°C as specified in GB / T 17931-1999;

[0103] S4. The two final polymers Poly-Ba1 and Poly-Ba2 were continuously fed into a mixer at a temperature of 250°C and a residence time of 1.5 h. The resulting polyester was then introduced into a twin-screw extruder, while 4.2 kg / h of hexamethylene diisocyanate (HDI) was metered in, and the temperature was set to 250°C. After a residence time of 3 minutes, the polyester was pelletized using an underwater pelletizer and then dried to obtain the final polyester product.

[0104] Embodiment 2:

[0105] S1. 491 kg / h of sebacic acid and 328 kg / h of 1,4-butanediol are continuously added to the slurry preparation kettle, and the prepared slurry is continuously fed into the first esterification reactor. The flow rate of 1,4-butanediol from the bottom of the process tower is 109 kg / h. At the same time, 0.49 kg / h of glycerol and 0.179 kg / h of n-butyl titanate are added. The pressure of the reactor is controlled to be 40 kPa (absolute pressure), the temperature is 190° C., the residence time is 2-4 h, and the water, tetrahydrofuran and butanediol generated by the reaction are removed to obtain an ester Ba1;

[0106] 355 kg / h of terephthalic acid and 289 kg / h of 1,4-butanediol were continuously added to the slurry preparation kettle, and the prepared slurry was continuously fed into the second esterification reactor. The flow rate of 1,4-butanediol from the bottom of the process tower was 96 kg / h. At the same time, 0.43 kg / h of glycerol and 0.331 kg / h of n-butyl titanate were added. The pressure of the reactor was controlled to be 40 kPa (absolute pressure), the temperature was 240°C, the residence time was 2-4 hours, and the water, tetrahydrofuran and butanediol generated by the reaction were removed to obtain the ester Ba2;

[0107] S2. The esterified product Ba1 is transferred into the first pre-polycondensation reactor, and 0.077 kg / h of n-butyl titanate and 0.198 kg / h of triphenyl phosphate are added at the same time. The temperature is 200°C, the pressure of the reactor is 4 kPa, the residence time is 2-3 hours, and the excess butanediol is extracted. At this time, the reaction product Pre-Ba1 reaches the viscosity number of 46 ml / g measured in a phenol / o-dichlorobenzene solution with a weight ratio of 1:1 in a constant temperature water bath at 25±0.05°C as specified in GB / T 17931-1999;

[0108] The esterified product Ba2 was transferred into the second pre-polycondensation reactor, and 0.142 kg / h of n-butyl titanate and 0.356 kg / h of triphenyl phosphate were added at the same time. The temperature was 250°C, the pressure of the reactor was 2 kPa, the residence time was 2-3 hours, and the excess butanediol was extracted. At this time, the reaction product Pre-Ba2 reached the viscosity of 37 ml / g measured in a phenol / o-dichlorobenzene solution with a weight ratio of 1:1 in a constant temperature water bath at 25±0.05°C as specified in GB / T 17931-1999;

[0109] S3. The prepolymer Pre-Ba1 is fed into the first final polymerization kettle through a melt pump. The temperature of the first final polymerization kettle is 220°C, the pressure is 120Pa, and the reaction time is 3-4 hours. At this time, the reaction product Poly-Ba1 reaches the viscosity of 151 ml / g measured in a phenol / o-dichlorobenzene solution with a weight ratio of 1:1 in a constant temperature water bath at 25±0.05°C as specified in GB / T 17931-1999;

[0110] The prepolymer Pre-Ba2 is fed into the second final polymerization kettle through a melt pump. The temperature of the second final polymerization kettle is 250°C, the pressure is 20Pa, and the reaction time is 3-4 hours. At this time, the reaction product Poly-Ba2 reaches the viscosity of 132 ml / g measured in a phenol / o-dichlorobenzene solution with a weight ratio of 1:1 in a constant temperature water bath at 25±0.05°C as specified in GB / T 17931-1999;

[0111] S4. The two final polymers Poly-Ba1 and Poly-Ba2 were continuously fed into a mixer at a temperature of 250°C and a residence time of 1.5 h. The resulting polyester was then introduced into a twin-screw extruder, while 4.2 kg / h of hexamethylene diisocyanate (HDI) was metered in, and the temperature was set to 250°C. After a residence time of 3 minutes, the polyester was pelletized using an underwater pelletizer and then dried to obtain the final polyester product.

[0112] Embodiment 3:

[0113] S1. 355 kg / h of adipic acid and 328 kg / h of 1,4-butanediol are continuously added to the slurry preparation kettle, and the prepared slurry is continuously fed into the first esterification reactor. The flow rate of 1,4-butanediol from the bottom of the process tower is 109 kg / h. At the same time, 0.179 kg / h of n-butyl titanate is added. The pressure of the reactor is controlled to be 40 kPa (absolute pressure), the temperature is 190° C., the residence time is 2-4 hours, and the water, tetrahydrofuran and butanediol generated by the reaction are removed to obtain an ester Ba1;

[0114] 355 kg / h of terephthalic acid and 289 kg / h of 1,4-butanediol were continuously added to the slurry preparation kettle, and the prepared slurry was continuously fed into the second esterification reactor. The flow rate of 1,4-butanediol from the bottom of the process tower was 96 kg / h. At the same time, 0.331 kg / h of n-butyl titanate was added. The pressure of the reactor was controlled to be 40 kPa (absolute pressure), the temperature was 240°C, the residence time was 2-4 hours, and the water, tetrahydrofuran and butanediol generated by the reaction were removed to obtain the ester Ba2;

[0115] S2. The esterified product Ba1 is transferred into the first pre-polycondensation reactor, and 0.077 kg / h of n-butyl titanate and 0.198 kg / h of triphenyl phosphate are added at the same time. The temperature is 200°C, the pressure of the reactor is 4 kPa, the residence time is 2-3 hours, and the excess butanediol is extracted. At this time, the reaction product Pre-Ba1 reaches the viscosity number of 33 ml / g measured in a phenol / o-dichlorobenzene solution with a weight ratio of 1:1 in a constant temperature water bath at 25±0.05°C as specified in GB / T 17931-1999;

[0116] The esterified product Ba2 was transferred into the second pre-polycondensation reactor, and 0.142 kg / h of n-butyl titanate and 0.356 kg / h of triphenyl phosphate were added at the same time. The temperature was 250°C, the pressure of the reactor was 2 kPa, the residence time was 2-3 hours, and the excess butanediol was extracted. At this time, the reaction product Pre-Ba2 reached the viscosity of 27 ml / g measured in a phenol / o-dichlorobenzene solution with a weight ratio of 1:1 in a constant temperature water bath at 25±0.05°C as specified in GB / T 17931-1999;

[0117] S3. The prepolymer Pre-Ba1 is fed into the first final polymerization kettle through a melt pump. The temperature of the first final polymerization kettle is 220°C, the pressure is 120Pa, and the reaction time is 3-4 hours. At this time, the reaction product Poly-Ba1 reaches the viscosity of 134 ml / g measured in a phenol / o-dichlorobenzene solution with a weight ratio of 1:1 in a constant temperature water bath at 25±0.05°C as specified in GB / T 17931-1999;

[0118] The prepolymer Pre-Ba2 is fed into the second final polymerization kettle through a melt pump. The temperature of the second final polymerization kettle is 250°C, the pressure is 20Pa, and the reaction time is 3-4 hours. At this time, the reaction product Poly-Ba2 reaches the viscosity of 128 ml / g measured in a phenol / o-dichlorobenzene solution with a weight ratio of 1:1 in a constant temperature water bath at 25±0.05°C as specified in GB / T 17931-1999;

[0119] S4. The two final polymers Poly-Ba1 and Poly-Ba2 were continuously fed into a mixer at a temperature of 250°C and a residence time of 1.5 h. The resulting polyester was then introduced into a twin-screw extruder, while 4.2 kg / h of hexamethylene diisocyanate (HDI) was metered in, and the temperature was set to 250°C. After a residence time of 3 minutes, the polyester was pelletized using an underwater pelletizer and then dried to obtain the final polyester product.

[0120] Embodiment 4:

[0121] S1. 355 kg / h of adipic acid and 328 kg / h of 1,4-butanediol are continuously added to the slurry preparation kettle, and the prepared slurry is continuously fed into the first esterification reactor. The flow rate of 1,4-butanediol from the bottom of the process tower is 109 kg / h. At the same time, 0.49 kg / h of glycerol and 0.179 kg / h of n-butyl titanate are added. The pressure of the reactor is controlled to be 40 kPa (absolute pressure), the temperature is 190° C., the residence time is 2-4 h, and the water, tetrahydrofuran and butanediol generated by the reaction are removed to obtain an ester Ba1;

[0122] 500kg / h of terephthalic acid and 407kg / h of 1,4-butanediol were continuously added to the slurry preparation kettle, and the prepared slurry was continuously fed into the second esterification reactor. The flow rate of 1,4-butanediol from the bottom of the process tower was 136kg / h. At the same time, 0.61kg / h of glycerol and 0.466kg / h of n-butyl titanate were added. The pressure of the reactor was controlled to be 40kPa (absolute pressure), the temperature was 240°C, the residence time was 2-4h, the water, tetrahydrofuran and butanediol generated by the reaction were removed, and the ester Ba2 was obtained.

[0123] S2. The esterified product Ba1 is transferred into the first pre-polycondensation reactor, and 0.077 kg / h of n-butyl titanate and 0.198 kg / h of triphenyl phosphate are added at the same time. The temperature is 200°C, the pressure of the reactor is 4 kPa, the residence time is 2-3 hours, and the excess butanediol is extracted. At this time, the reaction product Pre-Ba1 reaches the viscosity number of 44 ml / g measured in a phenol / o-dichlorobenzene solution with a weight ratio of 1:1 in a constant temperature water bath at 25±0.05°C as specified in GB / T 17931-1999;

[0124] The esterified product Ba2 was transferred into the second pre-polycondensation reactor, and 0.200 kg / h of n-butyl titanate and 0.501 kg / h of triphenyl phosphate were added at the same time. The temperature was 250°C, the pressure of the reactor was 2 kPa, the residence time was 2-3 hours, and the excess butanediol was extracted. At this time, the reaction product Pre-Ba2 reached the viscosity of 29 ml / g measured in a phenol / o-dichlorobenzene solution with a weight ratio of 1:1 in a constant temperature water bath at 25±0.05°C as specified in GB / T 17931-1999;

[0125] S3. The prepolymer Pre-Ba1 is fed into the first final polymerization kettle through a melt pump. The temperature of the first final polymerization kettle is 220°C, the pressure is 120Pa, and the reaction time is 3-4 hours. At this time, the reaction product Poly-Ba1 reaches the viscosity of 142 ml / g measured in a phenol / o-dichlorobenzene solution with a weight ratio of 1:1 in a constant temperature water bath at 25±0.05°C as specified in GB / T 17931-1999;

[0126] The prepolymer Pre-Ba2 is fed into the second final polymerization kettle through a melt pump. The temperature of the second final polymerization kettle is 250°C, the pressure is 20Pa, and the reaction time is 3-4 hours. At this time, the reaction product Poly-Ba2 reaches the viscosity of 133 ml / g measured in a phenol / o-dichlorobenzene solution with a weight ratio of 1:1 in a constant temperature water bath at 25±0.05°C as specified in GB / T 17931-1999;

[0127] S4. The two final polymers Poly-Ba1 and Poly-Ba2 were continuously fed into a mixer at a temperature of 250°C and a residence time of 1.5 h. The resulting polyester was then introduced into a twin-screw extruder, while 5.03 kg / h of hexamethylene diisocyanate (HDI) was metered in, and the temperature was set to 250°C. After a residence time of 3 minutes, the polyester was pelletized using an underwater pelletizer and then dried to obtain the final polyester product.

[0128] Embodiment 5:

[0129] S1. 355 kg / h of adipic acid and 328 kg / h of 1,4-butanediol are continuously added to the slurry preparation kettle, and the prepared slurry is continuously fed into the first esterification reactor. The flow rate of 1,4-butanediol from the bottom of the process tower is 109 kg / h. At the same time, 0.49 kg / h of glycerol and 0.179 kg / h of n-butyl titanate are added. The pressure of the reactor is controlled to be 40 kPa (absolute pressure), the temperature is 190° C., the residence time is 2-4 h, and the water, tetrahydrofuran and butanediol generated by the reaction are removed to obtain an ester Ba1;

[0130] 355 kg / h of terephthalic acid and 289 kg / h of 1,4-butanediol were continuously added to the slurry preparation kettle, and the prepared slurry was continuously fed into the second esterification reactor. The flow rate of 1,4-butanediol from the bottom of the process tower was 96 kg / h. At the same time, 0.43 kg / h of glycerol and 0.331 kg / h of n-butyl titanate were added. The pressure of the reactor was controlled to be 40 kPa (absolute pressure), the temperature was 240°C, the residence time was 2-4 hours, and the water, tetrahydrofuran and butanediol generated by the reaction were removed to obtain the ester Ba2;

[0131] S2. The esterified product Ba1 is transferred into the first pre-polycondensation reactor, and 0.077 kg / h of n-butyl titanate and 0.198 kg / h of triphenyl phosphate are added at the same time. The temperature is 200°C, the pressure of the reactor is 8 kPa, the residence time is 2-3 hours, and the excess butanediol is extracted. At this time, the reaction product Pre-Ba1 reaches the viscosity number of 31 ml / g measured in a phenol / o-dichlorobenzene solution with a weight ratio of 1:1 in a constant temperature water bath at 25±0.05°C as specified in GB / T 17931-1999;

[0132] The esterified product Ba2 was transferred into the second pre-polycondensation reactor, and 0.142 kg / h of n-butyl titanate and 0.356 kg / h of triphenyl phosphate were added at the same time. The temperature was 250°C, the pressure of the reactor was 8 kPa, the residence time was 2-3 hours, and the excess butanediol was extracted. At this time, the reaction product Pre-Ba2 reached the viscosity of 21 ml / g measured in a phenol / o-dichlorobenzene solution with a weight ratio of 1:1 in a constant temperature water bath at 25±0.05°C as specified in GB / T 17931-1999;

[0133] S3. The prepolymer Pre-Ba1 is fed into the first final polymerization kettle through a melt pump. The temperature of the first final polymerization kettle is 220°C, the pressure is 300Pa, and the reaction time is 3-4 hours. At this time, the reaction product Poly-Ba1 reaches the viscosity of 116 ml / g measured in a phenol / o-dichlorobenzene solution with a weight ratio of 1:1 in a constant temperature water bath at 25±0.05°C as specified in GB / T 17931-1999;

[0134] The prepolymer Pre-Ba2 is fed into the second final polymerization kettle through a melt pump. The temperature of the second final polymerization kettle is 250°C, the pressure is 200Pa, and the reaction time is 3-4 hours. At this time, the reaction product Poly-Ba2 reaches the viscosity of 105 ml / g measured in a phenol / o-dichlorobenzene solution with a weight ratio of 1:1 in a constant temperature water bath at 25±0.05°C as specified in GB / T 17931-1999;

[0135] S4. The two final polymers Poly-Ba1 and Poly-Ba2 were continuously fed into a mixer at a temperature of 250°C and a residence time of 1.5 h. The resulting polyester was then introduced into a twin-screw extruder, while 4.2 kg / h of hexamethylene diisocyanate (HDI) was metered in, and the temperature was set to 250°C. After a residence time of 3 minutes, the polyester was pelletized using an underwater pelletizer and then dried to obtain the final polyester product.

[0136] Embodiment 6:

[0137] S1. 355 kg / h of adipic acid and 219 kg / h of 1,4-butanediol are continuously added to the slurry preparation kettle, and the prepared slurry is continuously fed into the first esterification reactor. The flow rate of 1,4-butanediol from the bottom of the process tower is 66 kg / h. At the same time, 0.49 kg / h of glycerol and 0.179 kg / h of n-butyl titanate are added. The pressure of the reactor is controlled to be 40 kPa (absolute pressure), the temperature is 190° C., the residence time is 2-4 h, and the water, tetrahydrofuran and butanediol generated by the reaction are removed to obtain an ester Ba1;

[0138] 355 kg / h of terephthalic acid and 193 kg / h of 1,4-butanediol were continuously added to the slurry preparation kettle, and the prepared slurry was continuously fed into the second esterification reactor. The flow rate of 1,4-butanediol from the bottom of the process tower was 58 kg / h. At the same time, 0.43 kg / h of glycerol and 0.331 kg / h of n-butyl titanate were added. The pressure of the reactor was controlled to be 40 kPa (absolute pressure), the temperature was 240°C, the residence time was 2-4 hours, and the water, tetrahydrofuran and butanediol generated by the reaction were removed to obtain the ester Ba2;

[0139] S2. The esterified product Ba1 is transferred into the first pre-polycondensation reactor, and 0.077 kg / h of n-butyl titanate and 0.198 kg / h of triphenyl phosphate are added at the same time. The temperature is 200°C, the pressure of the reactor is 4 kPa, the residence time is 2-3 hours, and the excess butanediol is extracted. At this time, the reaction product Pre-Ba1 reaches the viscosity of 28 ml / g measured in a phenol / o-dichlorobenzene solution with a weight ratio of 1:1 in a constant temperature water bath at 25±0.05°C as specified in GB / T 17931-1999;

[0140] The esterified product Ba2 was transferred into the second pre-polycondensation reactor, and 0.142 kg / h of n-butyl titanate and 0.356 kg / h of triphenyl phosphate were added at the same time. The temperature was 250°C, the pressure of the reactor was 2 kPa, the residence time was 2-3 hours, and the excess butanediol was extracted. At this time, the reaction product Pre-Ba2 reached the viscosity of 21 ml / g measured in a phenol / o-dichlorobenzene solution with a weight ratio of 1:1 in a constant temperature water bath at 25±0.05°C as specified in GB / T 17931-1999;

[0141] S3. The prepolymer Pre-Ba1 is fed into the first final polymerization kettle through a melt pump. The temperature of the first final polymerization kettle is 220°C, the pressure is 120Pa, and the reaction time is 3-4 hours. At this time, the reaction product Poly-Ba1 reaches the viscosity of 96 ml / g measured in a phenol / o-dichlorobenzene solution with a weight ratio of 1:1 in a constant temperature water bath at 25±0.05°C as specified in GB / T 17931-1999;

[0142] The prepolymer Pre-Ba2 is fed into the second final polymerization kettle through a melt pump. The temperature of the second final polymerization kettle is 250°C, the pressure is 20Pa, and the reaction time is 3-4 hours. At this time, the reaction product Poly-Ba2 reaches the viscosity of 83 ml / g measured in a phenol / o-dichlorobenzene solution with a weight ratio of 1:1 in a constant temperature water bath at 25±0.05°C as specified in GB / T 17931-1999;

[0143] S4. The two final polymers Poly-Ba1 and Poly-Ba2 were continuously fed into a mixer at a temperature of 250°C and a residence time of 1.5 h. The resulting polyester was then introduced into a twin-screw extruder, while 4.2 kg / h of hexamethylene diisocyanate (HDI) was metered in, and the temperature was set to 250°C. After a residence time of 3 minutes, the polyester was pelletized using an underwater pelletizer and then dried to obtain the final polyester product.

[0144] Embodiment 7:

[0145] S1. 355 kg / h of adipic acid and 328 kg / h of 1,4-butanediol are continuously added to the slurry preparation kettle, and the prepared slurry is continuously fed into the first esterification reactor. The flow rate of 1,4-butanediol from the bottom of the process tower is 109 kg / h. At the same time, 0.49 kg / h of glycerol and 0.179 kg / h of n-butyl titanate are added. The pressure of the reactor is controlled to be 40 kPa (absolute pressure), the temperature is 190° C., the residence time is 2-4 h, and the water, tetrahydrofuran and butanediol generated by the reaction are removed to obtain an ester Ba1;

[0146] 355 kg / h of terephthalic acid and 289 kg / h of 1,4-butanediol were continuously added to the slurry preparation kettle, and the prepared slurry was continuously fed into the second esterification reactor. The flow rate of 1,4-butanediol from the bottom of the process tower was 96 kg / h. At the same time, 0.43 kg / h of glycerol and 0.331 kg / h of n-butyl titanate were added. The pressure of the reactor was controlled to be 40 kPa (absolute pressure), the temperature was 240°C, the residence time was 2-4 hours, and the water, tetrahydrofuran and butanediol generated by the reaction were removed to obtain the ester Ba2;

[0147] S2. The esterified product Ba1 is transferred into the first pre-polycondensation reactor, and 0.077 kg / h of n-butyl titanate and 0.198 kg / h of triphenyl phosphate are added at the same time. The temperature is 200°C, the pressure of the reactor is 4 kPa, the residence time is 2-3 hours, and the excess butanediol is extracted. At this time, the reaction product Pre-Ba1 reaches the viscosity number of 43 ml / g measured in a phenol / o-dichlorobenzene solution with a weight ratio of 1:1 in a constant temperature water bath at 25±0.05°C as specified in GB / T 17931-1999;

[0148] The esterified product Ba2 was transferred into the second pre-polycondensation reactor, and 0.142 kg / h of n-butyl titanate and 0.356 kg / h of triphenyl phosphate were added at the same time. The temperature was 250°C, the pressure of the reactor was 2 kPa, the residence time was 2-3 hours, and the excess butanediol was extracted. At this time, the reaction product Pre-Ba2 reached the viscosity of 37 ml / g measured in a phenol / o-dichlorobenzene solution with a weight ratio of 1:1 in a constant temperature water bath at 25±0.05°C as specified in GB / T 17931-1999;

[0149] S3. The prepolymer Pre-Ba1 is fed into the first final polymerization kettle through a melt pump. The temperature of the first final polymerization kettle is 220°C, the pressure is 120Pa, and the reaction time is 3-4 hours. At this time, the reaction product Poly-Ba1 reaches the viscosity of 136 ml / g measured in a phenol / o-dichlorobenzene solution with a weight ratio of 1:1 in a constant temperature water bath at 25±0.05°C as specified in GB / T 17931-1999;

[0150] The prepolymer Pre-Ba2 is fed into the second final polymerization kettle through a melt pump. The temperature of the second final polymerization kettle is 250°C, the pressure is 20Pa, and the reaction time is 3-4 hours. At this time, the reaction product Poly-Ba2 reaches the viscosity of 129 ml / g measured in a phenol / o-dichlorobenzene solution with a weight ratio of 1:1 in a constant temperature water bath at 25±0.05°C as specified in GB / T 17931-1999;

[0151] S4. The two final polymers of Poly-Ba1 and Poly-Ba2 were continuously fed into a mixer at a temperature of 250°C and a residence time of 2 hours. Then, the obtained polyester was introduced into a twin-screw extruder, pelletized by an underwater pelletizer, and then dried to obtain the final polyester product.

[0152] Embodiment 8:

[0153] S1. 355 kg / h of adipic acid and 328 kg / h of 1,4-butanediol are continuously added to the slurry preparation kettle, and the prepared slurry is continuously fed into the first esterification reactor. The flow rate of 1,4-butanediol from the bottom of the process tower is 109 kg / h. At the same time, 0.49 kg / h of glycerol and 0.179 kg / h of n-butyl titanate are added. The pressure of the reactor is controlled to be 40 kPa (absolute pressure), the temperature is 190° C., the residence time is 2-4 h, and the water, tetrahydrofuran and butanediol generated by the reaction are removed to obtain an ester Ba1;

[0154] 355 kg / h of terephthalic acid and 289 kg / h of 1,4-butanediol were continuously added to the slurry preparation kettle, and the prepared slurry was continuously fed into the second esterification reactor. The flow rate of 1,4-butanediol from the bottom of the process tower was 96 kg / h. At the same time, 0.43 kg / h of glycerol and 0.331 kg / h of n-butyl titanate were added. The pressure of the reactor was controlled to be 40 kPa (absolute pressure), the temperature was 240°C, the residence time was 2-4 hours, and the water, tetrahydrofuran and butanediol generated by the reaction were removed to obtain the ester Ba2;

[0155] S2. The esterified product Ba1 is transferred into the first pre-polycondensation reactor, and 0.077 kg / h of n-butyl titanate and 0.198 kg / h of triphenyl phosphate are added at the same time. The temperature is 200°C, the pressure of the reactor is 2 kPa, the residence time is 2-3 hours, and the excess butanediol is extracted. At this time, the reaction product Pre-Ba1 reaches the viscosity number of 51 ml / g measured in a phenol / o-dichlorobenzene solution with a weight ratio of 1:1 in a constant temperature water bath at 25±0.05°C as specified in GB / T 17931-1999;

[0156] The esterified product Ba2 was transferred into the second pre-polycondensation reactor, and 0.142 kg / h of n-butyl titanate and 0.356 kg / h of triphenyl phosphate were added at the same time. The temperature was 250°C, the pressure of the reactor was 1 kPa, the residence time was 2-3 hours, and the excess butanediol was extracted. At this time, the reaction product Pre-Ba2 reached the viscosity number of 43 ml / g measured in a phenol / o-dichlorobenzene solution with a weight ratio of 1:1 in a constant temperature water bath at 25±0.05°C as specified in GB / T 17931-1999;

[0157] S3. The prepolymer Pre-Ba1 is fed into the first final polymerization kettle through a melt pump. The temperature of the first final polymerization kettle is 220°C, the pressure is 80Pa, and the reaction time is 3-4 hours. At this time, the reaction product Poly-Ba1 reaches the viscosity of 163 ml / g measured in a phenol / o-dichlorobenzene solution with a weight ratio of 1:1 in a constant temperature water bath at 25±0.05°C as specified in GB / T 17931-1999;

[0158] The prepolymer Pre-Ba2 is fed into the second final polymerization kettle through a melt pump. The temperature of the second final polymerization kettle is 250°C, the pressure is 10Pa, and the reaction time is 3-4 hours. At this time, the reaction product Poly-Ba2 reaches the viscosity of 147 ml / g measured in a phenol / o-dichlorobenzene solution with a weight ratio of 1:1 in a constant temperature water bath at 25±0.05°C as specified in GB / T 17931-1999;

[0159] S4. The two final polymers Poly-Ba1 and Poly-Ba2 were continuously fed into a mixer at a temperature of 250°C and a residence time of 1.5 h. The resulting polyester was then introduced into a twin-screw extruder, while 4.2 kg / h of hexamethylene diisocyanate (HDI) was metered in, and the temperature was set to 250°C. After a residence time of 3 minutes, the polyester was pelletized using an underwater pelletizer and then dried to obtain the final polyester product.

[0160] Embodiment 9:

[0161] S1. 355 kg / h of adipic acid and 328 kg / h of 1,4-butanediol are continuously added to the slurry preparation kettle, and the prepared slurry is continuously fed into the first esterification reactor. The flow rate of 1,4-butanediol from the bottom of the process tower is 109 kg / h. At the same time, 0.49 kg / h of glycerol and 0.179 kg / h of n-butyl titanate are added. The pressure of the reactor is controlled to be 40 kPa (absolute pressure), the temperature is 190° C., the residence time is 2-4 h, and the water, tetrahydrofuran and butanediol generated by the reaction are removed to obtain an ester Ba1;

[0162] 355 kg / h of terephthalic acid and 289 kg / h of 1,4-butanediol were continuously added to the slurry preparation kettle, and the prepared slurry was continuously fed into the second esterification reactor. The flow rate of 1,4-butanediol from the bottom of the process tower was 96 kg / h. At the same time, 0.43 kg / h of glycerol and 0.331 kg / h of n-butyl titanate were added. The pressure of the reactor was controlled to be 40 kPa (absolute pressure), the temperature was 240°C, the residence time was 2-4 hours, and the water, tetrahydrofuran and butanediol generated by the reaction were removed to obtain the ester Ba2;

[0163] S2. The esterified product Ba1 is transferred into the first pre-polycondensation reactor, and 0.077 kg / h of n-butyl titanate and 0.198 kg / h of triphenyl phosphate are added at the same time. The temperature is 200°C, the pressure of the reactor is 4 kPa, the residence time is 2-2.5 h, and the excess butanediol is extracted. At this time, the reaction product Pre-Ba1 reaches the viscosity of 29 ml / g measured in a phenol / o-dichlorobenzene solution with a weight ratio of 1:1 in a constant temperature water bath at 25±0.05°C as specified in GB / T 17931-1999;

[0164] The esterified product Ba2 was transferred into the second pre-polycondensation reactor, and 0.142 kg / h of n-butyl titanate and 0.356 kg / h of triphenyl phosphate were added at the same time. The temperature was 250°C, the pressure of the reactor was 2 kPa, the residence time was 2-2.5 h, and the excess butanediol was extracted. At this time, the reaction product Pre-Ba2 reached the viscosity of 18 ml / g measured in a phenol / o-dichlorobenzene solution with a weight ratio of 1:1 in a constant temperature water bath at 25±0.05°C as specified in GB / T 17931-1999;

[0165] S3. The prepolymer Pre-Ba1 is fed into the first final polymerization kettle through a melt pump. The temperature of the first final polymerization kettle is 220°C, the pressure is 120Pa, and the reaction time is 2-3h. At this time, the reaction product Poly-Ba1 reaches the viscosity of 106 ml / g measured in a phenol / o-dichlorobenzene solution with a weight ratio of 1:1 in a constant temperature water bath at 25±0.05°C as specified in GB / T 17931-1999;

[0166] The prepolymer Pre-Ba2 is fed into the second final polymerization kettle through a melt pump. The temperature of the second final polymerization kettle is 250°C, the pressure is 20Pa, and the reaction time is 2-3h. At this time, the reaction product Poly-Ba2 reaches the viscosity of 95 ml / g measured in a phenol / o-dichlorobenzene solution with a weight ratio of 1:1 in a constant temperature water bath at 25±0.05°C as specified in GB / T 17931-1999;

[0167] S4. The two final polymers Poly-Ba1 and Poly-Ba2 were continuously fed into a mixer at a temperature of 250°C and a residence time of 1 h. The resulting polyester was then introduced into a twin-screw extruder, while 4.2 kg / h of hexamethylene diisocyanate (HDI) was metered in, and the temperature was set to 250°C. After a residence time of 3 minutes, the polyester was pelletized using an underwater pelletizer and then dried to obtain the final polyester product.

[0168] Comparative Example 1:

[0169] S1. 355 kg / h of terephthalic acid, 355 kg / h of adipic acid, 617 kg / h of 1,4-butanediol, 0.92 kg / h of glycerol and 0.51 kg / h of tetrabutyl orthotitanate are continuously added to a slurry preparation kettle, and the prepared slurry is continuously fed into an esterification reactor. The flow rate of 1,4-butanediol from the bottom of the process tower is 206 kg / h. The pressure of the reactor is controlled to be 40 kPa (absolute pressure), the temperature is 240°C, the residence time is 2-4 hours, and the water, tetrahydrofuran and butanediol generated by the reaction are removed to obtain an esterified product BA;

[0170] S2. The esterification product BA is introduced into the pre-polycondensation reactor by gravity, and 0.22 kg / h of n-butyl titanate and 0.55 kg / h of triphenyl phosphate are added at the same time. The temperature is 250°C, the pressure of the reactor is 2 kPa, the residence time is 2-3 hours, and the excess butanediol is extracted. At this time, the reaction product Pre-BA reaches the viscosity of 35 ml / g measured in a phenol / o-dichlorobenzene solution with a weight ratio of 1:1 in a constant temperature water bath at 25±0.05°C as specified in GB / T 17931-1999;

[0171] S3. The prepolymer Pre-BA is fed into a disc reactor (i.e., final polymerization reactor) through a melt pump. The temperature of the final polymerization reactor is 250°C, the pressure is 20Pa, and the reaction time is 3-4 hours. At this time, the reaction product Poly-BA reaches the viscosity of 133 ml / g as specified in GB / T17931-1999, which is measured in a phenol / o-dichlorobenzene solution with a weight ratio of 1:1 in a constant temperature water bath at 25±0.05°C;

[0172] S4. The obtained polyester was introduced into a twin-screw extruder, and 4.2 kg / h of hexamethylene diisocyanate (HDI) was metered in at the same time, and the temperature was set to 250° C. After a residence time of 3 minutes, the polyester was pelletized with an underwater pelletizer and then dried to obtain the final polyester product.

[0173] Comparative Example 2:

[0174] S1. 355 kg / h of adipic acid and 153 kg / h of 1,4-butanediol are continuously added to the slurry preparation kettle, and the prepared slurry is continuously fed into the first esterification reactor. The flow rate of 1,4-butanediol from the bottom of the process tower is 66 kg / h. At the same time, 0.49 kg / h of glycerol and 0.179 kg / h of n-butyl titanate are added. The pressure of the reactor is controlled to be 40 kPa (absolute pressure), the temperature is 190° C., the residence time is 2-4 h, and the water, tetrahydrofuran and butanediol generated by the reaction are removed to obtain an ester Ba1;

[0175] 355 kg / h of terephthalic acid and 135 kg / h of 1,4-butanediol were continuously added to the slurry preparation kettle, and the prepared slurry was continuously fed into the second esterification reactor. The flow rate of 1,4-butanediol from the bottom of the process tower was 58 kg / h. At the same time, 0.43 kg / h of glycerol and 0.331 kg / h of n-butyl titanate were added. The pressure of the reactor was controlled to be 40 kPa (absolute pressure), the temperature was 240°C, the residence time was 2-4 hours, and the water, tetrahydrofuran and butanediol generated by the reaction were removed to obtain the ester Ba2;

[0176] S2. The esterified product Ba1 is transferred into the first pre-polycondensation reactor, and 0.077 kg / h of n-butyl titanate and 0.198 kg / h of triphenyl phosphate are added at the same time. The temperature is 200°C, the pressure of the reactor is 4 kPa, the residence time is 2-3 hours, and the excess butanediol is extracted. At this time, the reaction product Pre-Ba1 reaches the viscosity of 15 ml / g measured in a phenol / o-dichlorobenzene solution with a weight ratio of 1:1 in a constant temperature water bath at 25±0.05°C as specified in GB / T 17931-1999;

[0177] The esterified product Ba2 was transferred into the second pre-polycondensation reactor, and 0.142 kg / h of n-butyl titanate and 0.356 kg / h of triphenyl phosphate were added at the same time. The temperature was 250°C, the pressure of the reactor was 2 kPa, the residence time was 2-3 hours, and the excess butanediol was extracted. At this time, the reaction product Pre-Ba2 reached the viscosity of 10 ml / g measured in a phenol / o-dichlorobenzene solution with a weight ratio of 1:1 in a constant temperature water bath at 25±0.05°C as specified in GB / T 17931-1999;

[0178] S3. The prepolymer Pre-Ba1 is fed into the first final polymerization kettle through a melt pump. The temperature of the first final polymerization kettle is 220°C, the pressure is 120Pa, and the reaction time is 3-4 hours. At this time, the reaction product Poly-Ba1 reaches the viscosity of 83 ml / g measured in a phenol / o-dichlorobenzene solution with a weight ratio of 1:1 in a constant temperature water bath at 25±0.05°C as specified in GB / T 17931-1999;

[0179] The prepolymer Pre-Ba2 is fed into the second final polymerization kettle through a melt pump. The temperature of the second final polymerization kettle is 250°C, the pressure is 20Pa, and the reaction time is 3-4 hours. At this time, the reaction product Poly-Ba2 reaches the viscosity of 62 ml / g measured in a phenol / o-dichlorobenzene solution with a weight ratio of 1:1 in a constant temperature water bath at 25±0.05°C as specified in GB / T 17931-1999;

[0180] S4. The two final polymers Poly-Ba1 and Poly-Ba2 were continuously fed into a mixer at a temperature of 250°C and a residence time of 1.5 h. The resulting polyester was then introduced into a twin-screw extruder, while 4.2 kg / h of hexamethylene diisocyanate (HDI) was metered in, and the temperature was set to 250°C. After a residence time of 3 minutes, the polyester was pelletized using an underwater pelletizer and then dried to obtain the final polyester product.

[0181] Comparative Example 3:

[0182] S1. 355 kg / h of adipic acid and 328 kg / h of 1,4-butanediol were continuously added to the slurry preparation kettle, and the prepared slurry was continuously fed to the first esterification reactor. The flow rate of 1,4-butanediol from the bottom of the process tower was 109 kg / h. At the same time, 0.49 kg / h of glycerol and 0.179 kg / h of n-butyl titanate were added. The pressure of the reactor was controlled to be 40 kPa (absolute pressure), the temperature was 190 ° C, the residence time was 2-3 h, and the water, tetrahydrofuran and butanediol generated by the reaction were removed to obtain an ester Ba1;

[0183] 355 kg / h of terephthalic acid and 289 kg / h of 1,4-butanediol were continuously added to the slurry preparation kettle, and the prepared slurry was continuously fed into the second esterification reactor. The flow rate of 1,4-butanediol from the bottom of the process tower was 96 kg / h. At the same time, 0.43 kg / h of glycerol and 0.331 kg / h of n-butyl titanate were added. The pressure of the reactor was controlled to be 40 kPa (absolute pressure), the temperature was 240°C, and the residence time was 2-3 hours. The water, tetrahydrofuran and butanediol generated by the reaction were removed to obtain the ester Ba2;

[0184] S2. The esterified product Ba1 is transferred into the first pre-polycondensation reactor, and 0.077 kg / h of n-butyl titanate and 0.198 kg / h of triphenyl phosphate are added at the same time. The temperature is 200°C, the pressure of the reactor is 4 kPa, the residence time is 1-2 hours, and the excess butanediol is extracted. At this time, the reaction product Pre-Ba1 reaches the viscosity of 25 ml / g measured in a phenol / o-dichlorobenzene solution with a weight ratio of 1:1 in a constant temperature water bath at 25±0.05°C as specified in GB / T 17931-1999;

[0185] The esterified product Ba2 was transferred into the second pre-polycondensation reactor, and 0.142 kg / h of n-butyl titanate and 0.356 kg / h of triphenyl phosphate were added at the same time. The temperature was 250°C, the pressure of the reactor was 2 kPa, the residence time was 1-2 hours, and the excess butanediol was extracted. At this time, the reaction product Pre-Ba2 reached the viscosity of 13 ml / g measured in a phenol / o-dichlorobenzene solution with a weight ratio of 1:1 in a constant temperature water bath at 25±0.05°C as specified in GB / T 17931-1999;

[0186] S3. The prepolymer Pre-Ba1 is fed into the first final polymerization kettle through a melt pump. The temperature of the first final polymerization kettle is 220°C, the pressure is 120Pa, and the reaction time is 30-60min. At this time, the reaction product Poly-Ba1 reaches the viscosity of 95 ml / g measured in a phenol / o-dichlorobenzene solution with a weight ratio of 1:1 in a constant temperature water bath at 25±0.05°C as specified in GB / T 17931-1999;

[0187] The prepolymer Pre-Ba2 is fed into the second final polymerization kettle through a melt pump. The temperature of the second final polymerization kettle is 250°C, the pressure is 20Pa, and the reaction time is 30-60min. At this time, the reaction product Poly-Ba2 reaches the viscosity of 76 ml / g measured in a phenol / o-dichlorobenzene solution with a weight ratio of 1:1 in a constant temperature water bath at 25±0.05°C as specified in GB / T 17931-1999;

[0188] S4. The two final polymers Poly-Ba1 and Poly-Ba2 were continuously fed into a mixer at a temperature of 250°C and a residence time of 30-60 min. The resulting polyester was then introduced into a twin-screw extruder, while 4.2 kg / h of hexamethylene diisocyanate (HDI) was metered in, and the temperature was set to 250°C. After a residence time of 2 minutes, the polyester was pelletized using an underwater pelletizer and then dried to obtain the final polyester product.

[0189] Table 1 Examples 1-9 and Comparative Examples 1-3

[0190]

[0191] From the above results, it can be seen that in Comparative Example 1, the mixed esterification step is used throughout the whole process, and the polymerization temperature is relatively high, so that the part of the semi-aromatic polyester derived from the aliphatic polyester is easily thermally degraded, and there are many side reactions, resulting in carboxyl groups and other non-hydroxycarboxyl terminals (such as double bonds, etc.), and the hydroxyl content of the semi-aromatic polyester is relatively low;

[0192] In Comparative Example 2, the alcohol-acid ratio is only 1.0, resulting in very low viscosity of the prepolymerization and polycondensation products, making chain extension difficult, and the resulting semi-aromatic polyester has very low hydroxyl groups, very high carboxyl groups, and low viscosity;

[0193] The polymerization reaction time of Comparative Example 3 is relatively short, so that the semi-aromatic polyester has a higher hydroxyl content and a lower viscosity. Due to the short reaction time, there is less thermal degradation and a lower carboxyl content.

[0194] Embodiment 10-18, comparative example 4-6:

[0195] According to the following weight parts,

[0196] Semi-aromatic polyester: 67; PLA: 10;

[0197] Calcium carbonate: 22;

[0198] Epoxy copolymer: 0.5;

[0199] Erucamide: 0.2;

[0200] The above materials are mixed and then put into a twin-screw extruder, extruded and granulated at 170-210° C. to obtain a semi-aromatic polyester composition.

[0201] PLA was purchased from Natureworks, USA, brand 4060D;

[0202] Calcium carbonate was purchased from Jiangsu Yifeng Powder Raw Materials Co., Ltd., brand YF-2350;

[0203] Epoxy copolymer was purchased from BASF, brand name Joncryl® ADR 4370;

[0204] Erucic acid amide was purchased from Jiangxi Weike Oil Chemical Co., Ltd., brand WK1890.

[0205] Table 2

[0206]

[0207] From the above results, it can be seen that Examples 10-18 use PBAT resins with suitable hydroxyl groups, and the tensile strength of the obtained semi-aromatic polyester compositions is above 300 MPa and the tear strength is above 1000 mN, both of which can meet the use requirements; the PBAT resins used in Comparative Examples 4 and 5 have a low hydroxyl content, resulting in poor compatibility between PBAT and PLA, and the tensile strength and tear strength of the obtained semi-aromatic polyester compositions are seriously reduced; the PBAT resin used in Comparative Example 6 has too high a hydroxyl content, and the tensile strength and tear strength of the obtained semi-aromatic polyester composition are also very low.

Claims

1. A semi-aromatic polyester derived from repeating units consisting of: The first component A, based on the total molar amount of the first component A, comprises: a1) 40-60 mol % of at least one aliphatic dicarboxylic acid or a derivative thereof; The aliphatic dicarboxylic acid or its derivative is selected from one or a mixture of oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, undecanedioic acid, 1,12-dodecanedicarboxylic acid, hexadecanedioic acid, eicosanedioic acid or tetracosanedicarboxylic acid or its ester derivative or its anhydride derivative; a2) 40-60 mol% of at least one aromatic dicarboxylic acid or its derivative; the aromatic dicarboxylic acid or its derivative is selected from one or a mixture of terephthalic acid, isophthalic acid, naphthalene dicarboxylic acid or its ester derivative or its anhydride derivative; Second component B: 1,4-butanediol; The invention is characterized in that the content of hydroxyl groups connected to aliphatic dicarboxylic acid in the semi-aromatic polyester is 17-40 mmol / kg; the content of hydroxyl groups connected to aromatic dicarboxylic acid in the semi-aromatic polyester is 17-40 mmol / kg; and the total content of hydroxyl groups is 35-80 mmol / kg; The semi-aromatic polyester has a viscosity of 150-350 ml / g measured in a phenol / o-dichlorobenzene solution with a weight ratio of 1:1 in a constant temperature water bath at 25±0.05°C according to GB / T 17931-1999; The semi-aromatic polyester has a carboxyl content of 5-50 mmol / kg.

2. The semi-aromatic polyester according to claim 1, characterized in that The aliphatic dicarboxylic acid or its derivative is selected from one or two of adipic acid, sebacic acid or its ester derivative or its anhydride derivative.

3. The semi-aromatic polyester according to claim 1, characterized in that The aromatic dicarboxylic acid or its derivative is selected from terephthalic acid or its ester derivative or its anhydride derivative.

4. The semi-aromatic polyester according to any one of claims 1 to 3, characterized in that Based on the total molar amount of the first component A, the semi-aromatic polyester further contains 0.01-5.0 mol % of a third component C and 0.01-5.0 mol % of a fourth component D.

5. The semi-aromatic polyester according to claim 4, characterized in that The third component C is selected from one or more of tartaric acid, citric acid, malic acid, trimethylolpropane, trimethylolethane, pentaerythritol, polyether triol, glycerol, 1,3,5-trimethylol acid, 1,2,4-trimethylol acid, 1,2,4-trimethylol anhydride, 1,2,4,5-pyromellitic acid or pyromellitic dianhydride.

6. The semi-aromatic polyester according to claim 5, characterized in that The third component C is selected from trimethylolpropane, pentaerythritol or glycerol.

7. The semi-aromatic polyester according to claim 6, characterized in that The fourth component D is selected from one or more of isocyanates, isocyanurates, peroxides, epoxides, oxazolines, oxazines, lactams, carbodiimides or polycarbodiimides containing two or more functional groups.

8. The semi-aromatic polyester according to claim 1, characterized in that The semi-aromatic polyester has a carboxyl content of 10-30 mmol / kg.

9. The method for preparing a semi-aromatic polyester according to claim 1, characterized in that: The steps include: S1. According to the proportion, a1 in the first component A and the second component B are added to the slurry preparation kettle, the prepared slurry is transported to the first esterification reactor, the refluxed second component B and the catalyst are added to the first esterification reactor from another route, and the esterification reaction is carried out at 150-200° C. and 30-110 kPa for 2-4 hours to obtain the esterification product Ba1; according to the proportion, a2 in the first component A and the second component B are added to the slurry preparation kettle, the prepared slurry is transported to the second esterification reactor, the refluxed second component B and the catalyst are added to the second esterification reactor from another route, and the esterification reaction is carried out at 200-250° C. and 30-110 kPa for 2-4 hours to obtain the esterification product Ba2; S2. The esterification product Ba1 in step S1 is subjected to a primary polycondensation reaction at a reaction temperature of 170-220°C and a pressure of 1-10 kPa; The esterification product Ba2 in step S1 is subjected to a primary polycondensation reaction at a reaction temperature of 230-270° C. and a pressure of 1-10 kPa; the two are subjected to a primary polycondensation reaction independently until the respective reaction products reach a viscosity of 15-60 ml / g as specified in GB / T 17931-1999 in a phenol / o-dichlorobenzene solution with a weight ratio of 1:1 and measured in a constant temperature water bath at 25±0.05° C., to obtain primary polycondensation reaction products Pre-Ba1 and Pre-Ba2, respectively; S3. The product Pre-Ba1 of the primary polycondensation reaction obtained in step S2 is transferred to the first final polymerization kettle, the reaction temperature is 180-230°C, and the pressure is 10-500Pa; the product Pre-Ba2 of the primary polycondensation reaction obtained in step S2 is transferred to the second final polymerization kettle, the reaction temperature is 220-270°C, and the pressure is 10-500Pa; the two are independently subjected to polycondensation reaction until the reaction product reaches the viscosity of 50-180 ml / g measured in a phenol / o-dichlorobenzene solution with a weight ratio of 1:1 and a constant temperature water bath at 25±0.05°C as specified in GB / T17931-1999, and the final polymerization products Poly-Ba1 and Poly-Ba2 are obtained respectively; S4. The final polymerization products Poly-Ba1 and Poly-Ba2 obtained in step S3 are mixed and reacted in a mixer to obtain a semi-aromatic polyester, which reaches the viscosity of 150-300 ml / g as specified in GB / T 17931-1999, measured in a phenol / o-dichlorobenzene solution with a weight ratio of 1:1 in a constant temperature water bath at 25±0.05°C.

10. The method for preparing a semi-aromatic polyester according to claim 9, characterized in that: The method further comprises the step S5. The semi-aromatic polyester obtained in step S4 is added to the fourth component D to carry out a chain growth reaction at a reaction temperature of 200 to 270° C. The reaction residence time is 0.5 to 15 minutes, until the reaction product reaches a viscosity of 150 to 350 ml / g as specified in GB / T 17931-1999 in a phenol / o-dichlorobenzene solution with a weight ratio of 1:1 and measured in a constant temperature water bath at 25±0.05° C.

11. The method for preparing a semi-aromatic polyester according to claim 10, characterized in that: The reaction residence time is 2-5 minutes.

12. A semi-aromatic polyester molding composition, characterized in that In terms of weight percentage, the components include: 5-95 wt% of the semi-aromatic polyester according to any one of claims 1-8; 5-95wt% additives and / or other polymers; 0-70wt% reinforcement materials and / or fillers.

13. Use of the semi-aromatic polyester according to any one of claims 1 to 8 in the preparation of compostable products, characterized in that: The compostable and degradable product is fiber, film or container.

Citation Information

Patent Citations

  • Continuous production method for biodegradable aliphatic-aromatic copolyester

    CN102443149A

  • Semi-aromatic polyester and preparation method and application thereof

    CN112280026A